Gestão ambiental: um estudo em pequenas e médias indústrias de Lagarto e Itaporanga D Ajuda - Sergipe - Oliveira, Ailton Ribeiro de (2005)
Due to the lack of data, about environmental issues, which are really necessary to set up bounds for strategic effective actions that priorize and even lead to the formulation of public policies directed at attending sustainable development necessary to small and medium industries in Sergipe´s semiarid. We have researched on different industries in order to obtain a bigger range as well as a better comprehension of how the ecological variable affects semiarid industry. The methodology of this study focuses on a bibliographic review over the topic allied to a diagnose research of the environmental management situation at small and medium industries in Lagarto/SE and all medium industry in Itaporanga D´Ajuda/SE. Also, issues related to environmental aspects have been approached such as: potentially significative impacts as well as measures adopted, internal/external factors which press for environmental practices and management procedures. Despite environmental management is still an unknown theme among industries, they recognize the importance of environmental inspection. Yet, it was observed that they devote themselves entirely to get environmental certification, especially, medium industries, which are interested in exportation. The most important environmental aspects concern to energy consumption and reuse of solid waste. The lack of management in those waste control and the difficulties to reuse and recycle account for one of the most serious environmental impacts observed in this research. In spite of having little information, about several environmental programs, a great deal of medium industries are already using some procedures related to environmental practices. It follows that, the biggest obstacles faced by those industries, concerning to environmental management, is the lack of: environmental agencies´ support, technical information and a policy which provides specific incentive to small and medium industry.